2014
DOI: 10.1007/s40670-014-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

A Multimedia Audience Response Game Show for Medical Education

Abstract: Games are increasingly popular in medical education. However, there is a need for games that target today's learners, including their preferences for active participation, social interaction, immediate feedback, and multimedia formats. With these preferences in mind, a commercially available game show template was used to develop a game show for review of medical microbiology. The game show was combined with an audience response system ("clickers") to enable participation of all students in a large group setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(49 reference statements)
0
12
0
1
Order By: Relevance
“…Our experience In addition, the TEAL-MEd committee members have recently published a description of Bravo games for formative assessment, including student perceptions of this TEAL-MEd format. 38 We are currently preparing manuscripts describing gamification of TurningPoint, student clinical reasoning, collaboration and engagement during DecisionSim activities, and student perceptions of the effectiveness of Prognosis-ATSU games for student learning. During these activities, we have observed students collaborating and faculty evolving in their new roles as guides on the side.…”
Section: Discussionmentioning
confidence: 99%
“…Our experience In addition, the TEAL-MEd committee members have recently published a description of Bravo games for formative assessment, including student perceptions of this TEAL-MEd format. 38 We are currently preparing manuscripts describing gamification of TurningPoint, student clinical reasoning, collaboration and engagement during DecisionSim activities, and student perceptions of the effectiveness of Prognosis-ATSU games for student learning. During these activities, we have observed students collaborating and faculty evolving in their new roles as guides on the side.…”
Section: Discussionmentioning
confidence: 99%
“…The core elements of active learning, student activity and engagement, are central to educational game theory [ 18 – 21 ]. Games are growing in popularity at all levels of education, including medical education [ 22 35 ], and include simulations, virtual environments, social and cooperative play, and alternative reality games [ 18 ]. A survey of family medicine and internal medicine residency programs directors in the United States indicated that 80 % used games as an educational strategy in their residency training programs [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Games, mobile applications, and virtual patient simulations can be used in medical curricula to promote learning, 11,[17][18][19] engagement, 20,21 collaboration, [22][23][24] realworld application, 25 clinical decision making, 18 distance training, 8 learning analytics, 16 and swift feedback. 6 views, textbooks on education game instruction, and Table 1).…”
Section: Potential Education Advantages Of Gamified Training Platformsmentioning
confidence: 99%
“…Gamified training platforms that we identified for preclinical training included 5 electronic games (some with audience response systems 20 and some accessed online) and 4 mobile applications. Table 2 lists these resources by platform type and summarizes descriptions and advantages of each platform.…”
Section: Preclinical Trainingmentioning
confidence: 99%